Level set based structural topology optimization for minimizing frequency response - Shu, Lei; Wang, Michael Yu; Fang, Zongde; Ma, Zhengdong; Wei, Peng (Journal of sound and vibration, 2011)
For the purpose of structure vibration reduction, a structural topology optimization for minimizing frequency response is proposed based on the level set method. The objective of the present study is to minimize the frequency response at the specified points or surfaces on the structure with an excitation frequency or a frequency range, subject to the given amount of the material over the admissible design domain. The sensitivity analysis with respect to the structural boundaries is carried out, while the Extended finite element method (X-FEM) is employed for solving the state equation and the adjoint equation. The optimal structure with smooth boundaries is obtained by the level set evolution with advection velocity, derived from the sensitivity analysis and the optimization algorithm. A number of numerical examples, in the frameworks of two-dimension (2D) and three-dimension (3D), are presented to demonstrate the feasibility and effectiveness of the proposed approach. ► We proposed a structural topology optimization for minimizing frequency response. ► Topology optimization base on the level set method. ► Optimal structure with smooth boundaries is obtained by the level set evolution. ► Frequency response of specified position on the structure is minimized.